ESTIMATION METHODS FOR ACOUSTIC IMPROVEMENT OF ROOMS USING MEASUREMENTS OF REVERBERATION TIME - Shevchenko, Yuliya S.; Beregovoj, Oleksandr M.; Kozlitin, Alexei A.; Kravchuk, Oksana Y. (Proceedings of National Aviation University (archive), 2008)
Estimation methods for reverberation time as a main approach for evaluation of premise acoustic characteristics has been considered. The veracity of results, obtained in reverberation camera has been proved. Assessment of acoustic characteristics of lecture-hall has been carried out.